SAXS measurements of the porosity in Cu(II)-doped SnO2 xerogels during crystallization - Brito, G. E. S. [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Elsevier, 1997)
The small-angle X-ray scattering (SAXS) technique was used to study the porosity which develops in Cu(II)-doped SnO2 monolithic xerogels during crystallization. The influence of the upper temperature of heat-treatment and of Cu(II) content on the structure was determined. Previous studies of the porosity in undoped SnO2 samples treated at temperatures ranging from 300 up to 600°C demonstrated the existence of a bimodal size distribution (one distribution was due to intra-aggregate and the other to inter-aggregate pores). However, the SAXS data from Cu(II)-doped samples heated to 500°C had a single mode distribution due only to inter-aggregate pores. Doped samples isothermically treated at 500°C were studied by the in situ SAXS technique. The time evolution of the scattering intensity function, or structure function of the porous material, exhibits a dynamical scaling property. The asymptotic behavior at high q (wave numbers) of the scaled function and consequently the nature and morphology of the porosity interface are a function of Cu(II) content. The kinetic exponents predicted by the statistical theory for the structure function suggest that the mechanism of porosity coarsening is controlled by surface diffusion. © 1997 Elsevier Science B.V.
Keywords: Crystallization; Diffusion in solids; Doping (additives); Heat treatment; Interfaces (materials); Morphology; Particle size analysis; Porosity; Porous materials; Reaction kinetics; X ray analysis; Monolithic xerogels; Small angle X ray scattering (SAXS); Sol-gels